Examining the Role of Financial Awareness, Attitude, and Knowledge in Personal Financial Planning: A Study in the Kathmandu Valley - Ghimire, Binod; Dahal, Rewan (The International Research Journal of Management Science, 2024)
Purpose. This study explores the relationship between financial literacy, including awareness, attitude, knowledge, and planning, among Nepalese individuals who reside in the Kathmandu Valley. Design/methodology/approach. The study employed a descriptive and causal research design based on the primary data collected from 386 respondents who were actively engaged in financial transactions at the Nepalese Stock Market. It used a purposive selection approach to select participants, specifically those involved in financial transactions at stock broker centers located in Kathmandu Valley. Findings. The study’s outcome indicates a modest positive relationship between financial awareness and individual financial planning (β = 0.143; p = 0.000), whereas financial attitude demonstrates a stronger positive association (β = 0.323; p = 0.000). Financial knowledge is the most influential component in individual financial planning (β = 0.501; p = 0.000). Research implications. The results indicate that by implementing focused educational programs, individuals can enhance their financial literacy, enable them to make well- informed financial decisions, enhance their financial planning skills, and ultimately progress their long-term financial security. Originality/value. This study underscores financial literacy's significance for individual and social well-being.